FACILITATED TUCKING EFFECTIVE TO PAIN RELIEF ON THE PRETERM INFANTS IN PERINATAL UNIT IN JAKARTA - Eva Oktaviani; Yeni Rustina; Defi Efendi (Jurnal Keperawatan Indonesia, 2018)
Most preterm infants often need to be hospitalized more than one week in intensive care, so they undergo numerous repeated painful procedures such as blood collection. The study aimed to identify the effect of facilitated tucking for pain respond that is physiological parameter and duration of crying in preterm infants during blood collection. The study design was quasi experimental with nonequivalent control group pretest-posttest design. Fourty babies were divided into two groups; the intervention group (n= 20) who received facilitated tucking during blood collection and the control group (n= 20) without facilitated tucking, with consecutive sampling technique. Statistical analyses used were General Linear Model+post hoc, Mann-Whitney, and Independent T-Test. There were significant means the difference in the heart rate, oxygen saturation, and duration of crying infants between non-intervention and intervention group. Duration of crying infants in intervention is shorter than the control group. Facilitated tucking is effective in pain reduction and crying time during blood collection. This finding implies a part of developmental care and should be attention for promoting pain management infants.Â Keywords: developmental care, facilitated tucking, pain, preterm infantsEfektivitas Facilitated Tucking Terhadap Respon Nyeri Bayi Prematur Selama Pengambilan Darah di Unit Perinatal di Jakarta. Mayoritas bayi prematur akan mengalami perawatan yang lama di ruang intensif, sehingga terpapar sejumlah prosedur menyakitkan berulang yang menimbulkan respon nyeri salah satunya pengambilan darah. Tujuan dari penelitian ini untuk mengidentifikasi pengaruh penerapan facilitated tucking terhadap respon nyeri berupa parameter fisiologis dan lama menangis selama dilakukan pengambilan darah. Desain penelitian adalah quasi experimental dengan nonequivalent control group pretest-posttest design. Empat puluh bayi pada sampel penelitian dibagi menjadi dua kelompok; kelompok intervensi (n= 20) dengan facilitated tucking dan kelompok kontrol (n= 20) tanpa facilitated tucking, diambil secara consecutive sampling. Analisis menggunakan uji General Linear Model+post hoc, Mann-Whitney, dan Independent T-Test. Ada perbedaan signifikan rerata frekuensi nadi, saturasi oksigen, dan lama menangis antara kedua kelompok selama pengambilan darah. Lama menangis pada kelompok intervensi menjadi lebih singkat. Facilitated tucking efektif mengurangi nyeri dan lama menangis selama pengambilan darah. Facilitated tucking dapat diterapkan sebagai bagian dari asuhan perkembangan untuk mendukung program pengendalian nyeri pada neonatus.Â Kata kunci: asuhan perkembangan, bayi prematur, facilitated tucking, nyeri